Farmakoedukasi Literasi Kesehatan Mental dan NAPZA untuk Siswa SMA/SMK - Aminah Dalimunthe; Khairunnisa Khairunnisa; Lisda Rimayani Nasution; Chemayanti Surbakti (Jurnal Surya Masyarakat, 2025)
Global data shows that one in seven children aged 10-19 experiences mental health disorders. In Indonesia, one in three adolescents (34.9%), equivalent to 15.5 million Indonesian adolescents, experiences at least one mental health issue per year. Mental health disorders are often associated with the use of NAPZA (Narcotics, Psychotropics, and Addictive Substances). This activity aims to enhance the knowledge and awareness of  9th state vocational high school  students about mental health and NAPZA. The community service activities involve socialization and education on mental health and NAPZA abuse, training using Positive bottle and an unspoken word book, and training with "Serene"  application (Self-care, Emotional Resilience, and Empowerment Network for Everyone) as a tool for education and consultation for the students of of  9th state vocational school students Medan. The community service activity successfully improved the understanding of  9th state vocational school students about mental health and the dangers of NAPZA. Education through lectures, demonstrations, and the Serene application showed positive impacts, with students' knowledge increasing from 40% to 60%. The Serene application was considered user-friendly and received positive feedback, supporting students' awareness of the importance of maintaining mental health and preventing NAPZA abuse.